1172 APPLYING THE NATIONAL STANDARDS OF PERIOPERATIVE CARE OF OLDER PEOPLE UNDERGOING EMERGENCY LAPAROTOMY (NELA). (16th January 2023) - Robinson, P
Abstract: Introduction: There are well documented in-equalities for outcomes for surgical intervention associated with Age and Frailty including emergency laparotomy. NELA data has shown over half of such patients are over 65 years old about one fifth are over 80. These patients having significantly higher mortality, longer hospital stays and it has also shown frailty to be an independent marker of poor outcomes. Through application of key standards these outcomes have improved however input from "consultant geriatrician-led MDT" remains stubbornly low nationally. Aims: To improve local Trust performance in meeting the NELA standard: "Peri-operative assessment by a member of the Geriatrician-Led MDT for frail (CFS 5+) patients 65 or older" to >80% (Green: ≥80%, Amber: 50 – 79% Red: <50%) of estimated 100 patients per year. Methods: 1. Proactive case finding with general surgical teams; 2. Engagement with Emergency Surgical Committee and NELA leads; 3. Improved our own electronic referral system; 4. Assist in development of electronic booking system with emergency laparotomy cases Results: We showed a significant improved in meeting the NELA standard from the red zone (Mean: 33% range 5% to 35%) into the amber with a of mean 60% (quartile range 52% to 78%) but still remains below our target with significant quarterly variation seen. All referrals and assessment remain post-intervention. Limitations in measures: Large variations in Frailty assessment and referral process (prospective Vs retrospective) Process rather than a Quality measure No balancing measures - Is there Reduced service elsewhere? Conclusions: Following a number of change ideas and despite challenging COVID related staffing issues we showed that a combination of key stakeholder engagement, proactive case-finding and improved referral processes we have improved Geriatrician input in frail patients undergoing emergency laparotomy. We suspect due to the non-systematic assessment of frailty that we may be missing some patients and or seeing late in care pathway.